Coral settlement induction by tetrabromopyrrole is widespread among Caribbean corals and compound specific - Sneed, Jennifer M.; Demko, Alyssa M.; Miller, Margaret W.; Yi, Dongqi; Moore, Bradley S.; Agarwal, Vinayak; Paul, Valerie Jean (Frontiers in Marine Science, 2024)
Tetrabromopyrrole (TBP) is a readily biosynthesized marine proteobacterial compound that induces coral settlement (attachment and metamorphosis) at concentrations ranging from 50 – 250 ng ml-1 (0.13 – 0.65 µM). This suggests a great potential for the use of this compound as a settlement inducer for restoration purposes. However, the applicability and optimal concentration of TBP for many coral species is not yet known. Furthermore, TBP is an unstable compound, which may present both challenges and benefits to its potential use for restoration purposes. In order to assess the utility of this compound for restoration, settlement induction by TBP was assessed among a wide range of Caribbean coral species. Additionally, a suite of halogenated compounds (tribromopyrrole, pentabromopseudolin, dibromophenol, tribromophenol, bromophene, n-methyl tetrabromopyrrole, tetrachloropyrrole, dibromoindole, n-methyl tetrachloropyrrole and dibromopyridine) that are related to TBP, some of which have similar antibiotic and antialgal properties, were also tested for settlement induction activity. These compounds were chosen based on their structural similarity to TBP or their identity as a product within the bacterial TBP biosynthetic pathway. TBP induced settlement in nine of ten coral species tested including seven not previously reported (Dendrogyra cylindrus, Orbicella faveolata, Colpophyllia natans, Diploria labyrinthiformis, Pseudodiploria clivosa, Acropora cervicornis, Montastraea cavernosa) at concentrations ranging from 0.375 – 1.5 µM. No other compound tested induced settlement, demonstrating a high degree of specificity for TBP.